Optimasi Thermal Oil Heater Menggunakan PSO Sebagai Tunning PID Controller - Enggal Indra Gunawan; Machrus Ali; Hidayatul Nurohmah (Nucleus Journal, 2022)
Optimasi Optimization of the auto temperature control system on the thermal oil heater system using PSO as a PID Controller tunning. Making a PSO-based Simulink tuning PID controller for thermal oil heater temperature in the 2013a Matlab program. Thermal oil heater simulation using PSO as a PID Controller tunning is the best result among other design methods. With kp = 2,057, ki = 1.337, kd = 0.148, we get an overshot value of = 0.002, undershot = 0, at a settling time of 4.521 seconds. This shows that the PID-PSO controller is the best method with the smallest overshot at 0.002, the smallest undershot at 0, and the fastest settling time at 4.521 seconds.